KELOMPOK PENGRAJIN LIMBAH PISANG DI DESA BONGKI LENGKESE KABUPATEN SINJAI - Riskasari,; Arfah, Sitti Rahmawati; Syarif, Ahmad; Suhaeman, Indra (Panrita Abdi - Jurnal Pengabdian pada Masyarakat, 2022)
Banana frond craft is a creative industry that utilizes banana fronds to be processed into handicrafts such as bossara, tissue holders, pen holders, and baskets. The initial obstacle was passive group members, so limited human resources resulted in a limited number of productions, in addition to management with traditional systems, and the results of weaving were still plain and monotonous. Also, the location of product marketing is not yet clear, so production is still based on orders, not stock in large quantities. Through this PKM activity, training and mentoring will be carried out to increase the production of woven banana midrib in terms of quantity (amount), quality, and efforts to build a marketing network. This PKM aims to increase the community's economic income through the utilization of the local potential of the village. PKM implementation methods include; (1) Organizational management training to activate KUB members and build a product marketing network. (2) Socialization and training aim to increase public interest and knowledge in processing banana waste into economic value products. (3) Assistance in making Bossara aims to improve skills in making quality Bossara with unique and varied designs through weaving practices to finishing product manufacture. The result of the service is the formation of an official group with funds for developing the village's creative economy; the bossara design becomes more refined and varied. Product promotion on social media and online advertising succeeded in increasing product sales. --- Kerajinan pelepah pisang merupakan industri kreatif yang memanfaatkan pelepah pisang diolah menjadi kerajinan tangan seperti, bossara, tempat tissu, tempat pulpen dan bakul. Kendala awal berupa anggota kelompok yang pasif sehingga keterbatasan tenaga menyebabkan jumlah produksi terbatas, selain itu pengelolaan dengan sistem tradisional sehingga hasil anyaman masih polos dan terkesan monoton. Serta, lokasi pemasaran produk yang belum jelas sehingga produksi masih berbasis pesanan bukan persediaan stock dalam jumlah banyak. Melalui kegiatan PKM ini akan dilakukan pelatihan dan pendampingan untuk meningkatkan produksi anyaman pelepah pisang dari segi kuantitas (jumlah), kualitas serta upaya membangun jaringan pemasarannya. PKM ini bertujuan menambah penghasilan ekonomi masyarakat melalui pemanfaatan potensi lokal desa. Metode pelaksanaan PKM meliputi; (1) Pelatihan manajemen organisasi untuk mengaktifkan anggota KUB serta membangun jaringan pemasaran produk. (2) Sosialisasi dan pelatihan bertujuan meningkatkan minat dan pengetahuan masyarakat dalam mengolah limbah pisang menjadi produk yang bernilai ekonomis. (3) Pendampingan pembuatan Bossara bertujuan meningkatkan keterampilan membuat Bossara berkualitas dengan desain unik dan bervariasi melalui praktek menganyam hingga finishing pembuatan produk. Hasil pengabdian berupa pembentukan kelompok resmi dengan dana pengembangan ekonomi kreatif desa, desain bossara menjadi lebih halus dan bervariasi. Promosi produk pada sosial media dan pemasangan iklan pada media online berhasil meningkatklan penjualan produk.